Rank/Rankl/opg: literature review - Silva, I (2011)
The discovery of the receptor activator of nuclear factor-kB (RANK)/RANK Ligand (RANKL)/osteoprotegerin (OPG) pathway contributed to the understanding of how bone formation and resorption were processed and regulated. RANKL and OPG are members of the tumor necrosis factor (TNF) and TNF receptor (TNFr) superfamilies, respectively, and binding to receptor activator of NF-kB (RANK) not only regulate osteoclast formation, activation and survival in normal bone modeling and remodeling, but also in several other pathologic conditions characterized by increased bone turnover. There is accumulating evidence of the potential role of OPG and RANKL in other tissues. Looking beyond the RANK/RANKL/OPG axis, Wingless (Wnt) pathway emerged as the osteoblast differentiation way, and also as a bone mass regulator. Researchers have been discovering new molecules and cytokines interactions. Altogether, data suggest that RANK/RANKL/OPG system could be targeted as a new treatment strategy in bone conditions. FREEDOM is the more recently published clinical trial about a RANKL-specific recombinant fully human monoclonal antibody (denosumab). OPG is also a potential innovative therapeutic option to be investigated.